Exterior material for all-solid-state battery, and all-solid-state battery

JP2024167918A5Active Publication Date: 2025-02-10TOPPAN HOLDINGS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024155249
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-02-10
Estimated Expiration
2042-02-02

AI Technical Summary

Technical Problem

The exterior material for all-solid-state batteries in existing technologies often experiences bubble formation during heat sealing due to moisture evaporation, leading to reduced sealing strength and potential gas leakage.

Method used

The exterior material is designed with a sealant layer having a moisture content of 2700 mass ppm or less, utilizing polyolefin or polyester films with a melting point of 150°C or higher, and incorporating a polyurethane adhesive to enhance heat resistance and suppress bubble generation.

Benefits of technology

This design effectively prevents bubble formation during heat sealing, maintaining sealing strength and preventing gas leakage, even in high-temperature environments, thereby ensuring the integrity of the all-solid-state battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide an exterior material for an all-solid-state battery, which can inhibit generation of air bubbles in a sealant layer during heat seal, and the all-solid-state battery.SOLUTION: An exterior material for an all-solid-state battery comprises at least a base material layer, a barrier layer, and a sealant layer provided in this order, in which a moisture content of the sealant layer is 2700 mass ppm or less. The sealant layer is made of, for example, a polyolefin film containing a polyolefin resin or a polyester film containing a polyester resin.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an exterior material for an all-solid-state battery and an all-solid-state battery. [Background technology]

[0002] In recent years, the development of all-solid-state batteries that can increase capacity has progressed rapidly. Unlike current lithium-ion batteries, all-solid-state batteries use a solid electrolyte, which allows them to be used at high temperatures that were not possible until now. This eliminates the need for battery cooling equipment, and is expected to lead to improved space efficiency, reduced costs, and lower power consumption.

[0003] Such an all-solid-state battery includes a battery body including a solid electrolyte and electrodes, and an exterior bag that houses the battery body, and the exterior bag is obtained by heat-sealing an exterior material. The exterior material for such an all-solid-state battery includes a base layer, a barrier layer, and a sealant layer in this order, and the sealant layer is made of a polyester film or the like to impart heat resistance (see, for example, Patent Document 1 below). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 6747636 (e.g., claim 5) Summary of the Invention [Problem to be solved by the invention]

[0005] However, the exterior material of the all-solid-state battery described in the above-mentioned Patent Document 1 has the following problems. That is, in the exterior packaging material of the all-solid-state battery described in the above-mentioned Patent Document 1, air bubbles were sometimes found all over the sealant layer during heat sealing.

[0006] The present disclosure has been made in consideration of the above problems, and has an object to provide an exterior material for an all-solid-state battery that can suppress the generation of air bubbles in a sealant layer during heat sealing, and an all-solid-state battery using the same. [Means for solving the problem]

[0007] The present inventors have studied the cause of the phenomenon in which bubbles are observed all over the sealant layer as described above. As a result, they have considered that the occurrence of bubbles all over the sealant layer may be caused by heat sealing the exterior material at a high temperature. That is, the present inventors considered that when the exterior material is heat sealed at a high temperature, the moisture in the sealant layer of the exterior material evaporates, and the generated bubbles expand all at once, easily combine with other bubbles, grow, and remain after cooling. The present inventors also considered that the above phenomenon may also be largely dependent on the moisture content in the sealant layer of the exterior material. Therefore, the present inventors have further conducted intensive research and have found that the above problem can be solved by the following disclosure.

[0008] That is, the present disclosure provides an exterior material for an all-solid-state battery comprising at least a base layer, a barrier layer, and a sealant layer in this order, wherein the water content of the sealant layer is 2700 ppm by mass or less.

[0009] According to the exterior material of the present disclosure, the generation of bubbles in the sealant layer during heat sealing can be suppressed. Therefore, the sealant layer is prevented from having coarse parts (parts with many bubbles) and dense parts (parts with few bubbles), which causes the seal strength to decrease in the coarse parts. Therefore, even if the battery body including the solid electrolyte expands due to the use of the all-solid-state battery in a high-temperature environment and a force acts on the exterior bag to open it, the exterior material can maintain the sealed state of the exterior bag obtained by heat sealing the exterior material. Therefore, even if gas such as hydrogen sulfide is generated in the exterior bag of the all-solid-state battery by the reaction between moisture and the sulfide-based solid electrolyte when the all-solid-state battery contains a sulfide-based solid electrolyte as a solid electrolyte in the exterior bag, leakage of such gas can be suppressed. In addition, since the generation of bubbles that easily become a passage for moisture is suppressed in the sealant layer, the intrusion of moisture from the outside of the exterior material is suppressed. Therefore, when the all-solid-state battery contains a sulfide-based solid electrolyte as a solid electrolyte in the exterior bag, the generation of gas such as hydrogen sulfide by the reaction between moisture and the sulfide-based solid electrolyte in the exterior bag of the all-solid-state battery can also be suppressed.

[0010] In the all-solid-state battery exterior material, the sealant layer is preferably a polyolefin film containing a polyolefin-based resin or a polyester film containing a polyester-based resin.

[0011] In this case, the sealing property is improved. In addition, since the polyolefin film and the polyester film have heat resistance, the exterior material can further improve the heat resistance of the all-solid-state battery.

[0012] In the all-solid-state battery exterior packaging material, it is preferable that the sealant layer is the polyolefin film, the polyolefin film includes an acid-modified polyolefin resin layer, and the acid-modified polyolefin resin layer is directly laminated to the barrier layer.

[0013] In this case, moisture is less likely to be taken in by the sealant layer than when the acid-modified polyolefin resin layer of the polyolefin film is directly laminated to the barrier layer and the acid-modified polyolefin resin layer of the polyolefin film and the barrier layer are bonded with a polyurethane-based adhesive used as a high-temperature resistant adhesive. Therefore, even if the exterior material is repeatedly exposed to high temperatures, moisture is less likely to be released from the sealant layer each time. Therefore, when the all-solid-state battery contains a sulfide-based solid electrolyte as a solid electrolyte in an exterior bag, it is possible to suppress the generation of hydrogen sulfide due to the reaction between the released moisture and sulfide.

[0014] In the all-solid-state battery exterior material, the sealant layer preferably has a melting point of 250° C. or lower.

[0015] In this case, since the sealant layer has a melting point of 250° C. or less, the heat sealing temperature can be reduced. Therefore, the generation of bubbles in the sealant layer during heat sealing can be further suppressed. Therefore, the deterioration of the seal strength and barrier property of the exterior material is further suppressed. Therefore, the exterior material can more sufficiently maintain the sealability of the exterior bag of the all-solid-state battery.

[0016] In the all-solid-state battery exterior material, the sealant layer preferably has a melting point of 150° C. or higher.

[0017] In this case, since the sealant layer has a melting point of 150° C. or more, even if the exterior material is used in a high-temperature environment, it is possible to suppress a decrease in the seal strength of the exterior material. Therefore, when an all-solid-state battery contains a sulfide-based solid electrolyte as a solid electrolyte in an exterior bag, even if gas such as hydrogen sulfide is generated by a reaction between moisture and the sulfide-based solid electrolyte in the exterior bag of the all-solid-state battery, leakage of such gas can be further suppressed.

[0018] The present disclosure also relates to an all-solid-state battery including a battery body having a solid electrolyte and an outer bag that houses the battery body, the outer bag being obtained by heat-sealing the outer casing material for an all-solid-state battery described above.

[0019] According to the all-solid-state battery of the present disclosure, the outer bag is obtained by heat-sealing the above-mentioned outer casing material for the all-solid-state battery. Here, according to the above-mentioned outer casing material, the generation of air bubbles in the sealant layer during heat sealing can be suppressed. Therefore, according to the all-solid-state battery of the present disclosure, the occurrence of rough and dense parts in the sealant layer of the outer casing material, which causes the seal strength to decrease in the rough parts, is suppressed. Therefore, even if the battery body expands due to use of the all-solid-state battery in a high-temperature environment and a force acts on the outer casing to open it, the all-solid-state battery can maintain the sealed state of the outer casing by the outer casing material. In addition, since the generation of air bubbles that easily become a passage for moisture is suppressed in the sealant layer, the intrusion of moisture from the outside of the outer casing material is suppressed. Therefore, when a sulfide-based solid electrolyte is used as the solid electrolyte, the generation of gas such as hydrogen sulfide due to the reaction between moisture and the sulfide-based solid electrolyte in the outer casing of the all-solid-state battery can also be suppressed.

[0020] In this disclosure, "melting point" means the "peak melting temperature" determined in accordance with the method described in JIS K7121-1987, and when two or more melting peaks appear independently, the lowest melting peak temperature is adopted.

[0021] In addition, in the present disclosure, when the sealant layer is a multilayer film, the melting point refers to the melting point of the layer that has the lowest melting point among the layers that constitute the multilayer film. Effect of the Invention

[0022] According to the present disclosure, there are provided an exterior material for an all-solid-state battery that can suppress the generation of air bubbles in a sealant layer during heat sealing, and an all-solid-state battery using the same. [Brief description of the drawings]

[0023] [Figure 1]FIG. 1 is a cross-sectional view illustrating a schematic diagram of an exterior material for an all-solid-state battery according to an embodiment of the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view illustrating a schematic diagram of an exterior material for an all-solid-state battery according to another embodiment of the present disclosure. [Diagram 3] FIG. 2 is a cross-sectional view that illustrates a schematic diagram of an exterior material for an all-solid-state battery according to still another embodiment of the present disclosure. [Figure 4] FIG. 1 is a perspective view showing an all-solid-state battery according to an embodiment of the present disclosure. [Diagram 5] FIG. 2 is a plan view showing a structure for obtaining evaluation samples in Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Hereinafter, preferred embodiments of the present disclosure will be described in detail with reference to the drawings. In the drawings, the same or corresponding parts are denoted by the same reference numerals, and duplicated explanations will be omitted. In addition, the dimensional ratios of the drawings are not limited to the ratios shown in the drawings.

[0025] [Exterior material for all-solid-state batteries] 1 is a cross-sectional view showing a schematic diagram of an all-solid-state battery exterior material according to an embodiment of the present disclosure. As shown in FIG. 1, an all-solid-state battery exterior material according to this embodiment (hereinafter, also simply referred to as an "exterior material") 10 includes a base layer 11, a first adhesive layer 12a, a barrier layer 13, a second adhesive layer 12b, and a sealant layer 16 in this order. Here, the moisture content of the sealant layer 16 is 2700 mass ppm or less. The exterior material 10 can more effectively suppress the generation of bubbles in the sealant layer 16 of the exterior material 10 during heat sealing of the exterior material 10, compared to a case in which the moisture content of the sealant layer 16 exceeds 2700 mass ppm.

[0026] The barrier layer 13 may have a first anti-corrosion treatment layer 14a on the substrate layer 11 side. The barrier layer 13 may have a second anti-corrosion treatment layer 14b on the sealant layer 16 side. In the exterior material 10, the substrate layer 11 is the outermost layer, and the sealant layer 16 is the innermost layer. That is, the exterior material 10 is used with the substrate layer 11 facing the exterior side of the all-solid-state battery, and the sealant layer 16 facing the interior side of the all-solid-state battery.

[0027] Each layer constituting the packaging material 10 will now be described in detail.

[0028] <Base material layer> The base layer 11 provides heat resistance in a sealing process when manufacturing an all-solid-state battery and plays a role in suppressing the occurrence of pinholes that may occur during molding and distribution. In particular, in the case of an exterior material for an all-solid-state battery for large-scale use, the base layer 11 can also provide scratch resistance, chemical resistance, insulation, and the like.

[0029] The base layer 11 is preferably a layer formed of an insulating resin, such as polyester resin, polyamide resin, polyimide resin, polyamideimide resin, polyetherketone resin, polyphenylene sulfide resin, polyetherimide resin, polysulfone resin, fluororesin, phenol resin, melamine resin, urethane resin, allyl resin, silicone resin, epoxy resin, furan resin, acetyl cellulose resin, or the like.

[0030] When these resins are applied to the base layer 11, they may be in the form of a stretched or unstretched film, or in the form of a coating film. The base layer 11 may be a single layer or a multilayer, and in the case of a multilayer, different resins may be used in combination. In the case of a film, a co-extrusion film or a film laminated with an adhesive may be used. In the case of a coating film, a film coated the number of times that it is laminated may be used, and a multilayer film may be formed by combining a film and a coating film.

[0031] Among these resins, polyester resin and polyamide resin are preferable for the base layer 11 because of their excellent moldability. Examples of polyester resin include polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. Examples of polyamide resin include nylon 6, nylon 6,6, a copolymer of nylon 6 and nylon 6,6, nylon 6, nylon 9T, nylon 10, polymetaxylylene adipamide (MXD6), nylon 11, and nylon 12.

[0032] When these resins are used in the form of a film, it is preferably a biaxially stretched film. Examples of the stretching method for the biaxially stretched film include sequential biaxial stretching, tubular biaxial stretching, and simultaneous biaxial stretching. From the viewpoint of obtaining better deep drawing formability, the biaxially stretched film is preferably one stretched by the tubular biaxial stretching method.

[0033] The thickness of the substrate layer 11 is preferably 6 to 50 μm, and more preferably 10 to 30 μm. When the thickness of the substrate layer 11 is 6 μm or more, the pinhole resistance and insulating properties of the packaging material 10 tend to be improved. When the thickness of the substrate layer 11 is 50 μm or less, the total thickness of the packaging material 10 can be reduced.

[0034] In order to suppress deformation of the base layer 11 during sealing, the melting point of the base layer 11 is higher than the melting point of the sealant layer 16, and is preferably higher than the melting point of the sealant layer 16 by 30° C. or more.

[0035] <First adhesive layer> The first adhesive layer 12a is a layer that bonds the base layer 11 and the barrier layer 13. Specific examples of materials constituting the first adhesive layer 12a include polyurethane resins in which a bifunctional or higher isocyanate compound (polyfunctional isocyanate compound) is reacted with a base material such as polyester polyol, polyether polyol, acrylic polyol, or carbonate polyol. The above-mentioned various polyols can be used alone or in combination of two or more types depending on the function and performance required for the exterior material 10. In addition to the above, a base material containing an epoxy resin and a curing agent can also be used, but is not limited to this. In addition, the above-mentioned adhesives may be mixed with various other additives and stabilizers depending on the performance required for the adhesive.

[0036] The thickness of the first adhesive layer 12a is not particularly limited, but from the viewpoint of obtaining desired adhesive strength, conformability, processability, and the like, the thickness is, for example, preferably 1 to 10 μm, and more preferably 2 to 7 μm.

[0037] <Barrier layer> The barrier layer 13 has a water vapor barrier property that prevents moisture from penetrating into the inside of the all-solid-state battery. The barrier layer 13 may also have extensibility for deep drawing. As the barrier layer 13, for example, various metal foils such as aluminum, stainless steel, copper, etc., or metal vapor deposition films, inorganic oxide vapor deposition films, carbon-containing inorganic oxide vapor deposition films, films provided with these vapor deposition films, etc. can be used. As the film provided with the vapor deposition film, for example, an aluminum vapor deposition film or an inorganic oxide vapor deposition film can be used. These can be used alone or in combination of two or more. As the barrier layer 13, a metal foil is preferable, and an aluminum foil is more preferable, in terms of mass (specific gravity), moisture resistance, processability, and cost.

[0038] As the aluminum foil, a soft aluminum foil that has been annealed can be preferably used from the viewpoint of imparting desired ductility during molding, but it is more preferable to use an aluminum foil containing iron for the purpose of imparting further pinhole resistance and ductility during molding. The content of iron in the aluminum foil is preferably 0.1 to 9.0 mass%, more preferably 0.5 to 2.0 mass%, in 100 mass% of the aluminum foil. When the iron content is 0.1 mass% or more, an exterior material 10 having better pinhole resistance and ductility can be obtained. When the iron content is 9.0 mass% or less, an exterior material 10 having better flexibility can be obtained. As the aluminum foil, an untreated aluminum foil may be used, but it is preferable to use an aluminum foil that has been degreased in terms of imparting corrosion resistance. When the aluminum foil is degreased, the degreased treatment may be performed on only one side of the aluminum foil, or on both sides.

[0039] The thickness of the barrier layer 13 is not particularly limited, but taking into consideration the barrier properties, pinhole resistance, and processability, it is preferably 9 to 200 μm, and more preferably 15 to 100 μm.

[0040] <First and second corrosion prevention treatment layers> The first and second corrosion prevention layers 14a and 14b are layers provided to prevent corrosion of the metal foil (metal foil layer) constituting the barrier layer 13. The first corrosion prevention layer 14a plays a role in increasing the adhesion between the barrier layer 13 and the first adhesive layer 12a. The second corrosion prevention layer 14b plays a role in increasing the adhesion between the barrier layer 13 and the second adhesive layer 12b. The first corrosion prevention layer 14a and the second corrosion prevention layer 14b may be layers of the same configuration or layers of different configurations. The first and second corrosion prevention layers 14a and 14b (hereinafter also simply referred to as "corrosion prevention layers 14a and 14b") are formed, for example, by degreasing treatment, hydrothermal conversion treatment, anodizing treatment, chemical conversion treatment, or a combination of these treatments.

[0041] Examples of the degreasing treatment include acid degreasing and alkaline degreasing. Examples of the acid degreasing include a method using an inorganic acid such as sulfuric acid, nitric acid, hydrochloric acid, or hydrofluoric acid alone or a mixture of these. In addition, by using an acid degreasing agent in which a fluorine-containing compound such as monosodium ammonium difluoride is dissolved in the inorganic acid as described above, not only can the aluminum be degreased, but also a passive aluminum fluoride can be formed, which is effective in terms of corrosion resistance, particularly when an aluminum foil is used for the barrier layer 13. Examples of the alkaline degreasing include a method using sodium hydroxide or the like.

[0042] An example of the hydrothermal modification treatment is boehmite treatment in which an aluminum foil is immersed in boiling water containing triethanolamine. An example of the anodization treatment is alumite treatment.

[0043] The chemical conversion treatment may be of the immersion type or the coating type. Examples of the immersion type chemical conversion treatment include chromate treatment, zirconium treatment, titanium treatment, vanadium treatment, molybdenum treatment, calcium phosphate treatment, strontium hydroxide treatment, cerium treatment, ruthenium treatment, and various chemical conversion treatments consisting of a mixture of these. On the other hand, examples of the coating type chemical conversion treatment include a method in which a coating agent having corrosion prevention properties is applied onto the barrier layer 13.

[0044] When forming at least a part of the corrosion prevention layer by any of these corrosion prevention treatments, namely, hydrothermal conversion treatment, anodizing treatment, and chemical conversion treatment, it is preferable to perform the above-mentioned degreasing treatment in advance. When using a degreased metal foil, such as a metal foil that has been subjected to an annealing process, as the barrier layer 13, there is no need to perform a degreasing treatment again in forming the corrosion prevention layers 14a and 14b.

[0045] The coating agent used in the spray-type chemical conversion treatment preferably contains trivalent chromium. The coating agent may also contain at least one polymer selected from the group consisting of cationic polymers and anionic polymers, which will be described later.

[0046] Among the above treatments, particularly in hydrothermal conversion treatment and anodization treatment, the aluminum foil surface is dissolved by a treatment agent to form an aluminum compound (boehmite, alumite) having excellent corrosion resistance. Therefore, since a bicontinuous structure is formed from the barrier layer 13 using the aluminum foil to the corrosion prevention treatment layers 14a, 14b, the above treatment is included in the definition of chemical conversion treatment. On the other hand, as described later, it is also possible to form the corrosion prevention treatment layers 14a, 14b by a pure coating method that is not included in the definition of chemical conversion treatment. As an example of this method, a method using a sol of a rare earth element oxide such as cerium oxide with an average particle size of 100 nm or less can be mentioned, which has an aluminum corrosion prevention effect (inhibitor effect) and is also environmentally friendly. By using this method, it is possible to impart a corrosion prevention effect to metal foils such as aluminum foils even with a general coating method.

[0047] Examples of the rare earth element oxide sol include sols using various solvents such as water-based, alcohol-based, hydrocarbon-based, ketone-based, ester-based, ether-based, etc. Among these, water-based sols are preferred.

[0048] In order to stabilize the dispersion of the rare earth oxide sol, inorganic acids such as nitric acid, hydrochloric acid, phosphoric acid, etc. or their salts, and organic acids such as acetic acid, malic acid, ascorbic acid, lactic acid, etc. are usually used as dispersion stabilizers. Among these dispersion stabilizers, phosphoric acid in particular is expected to provide the following in the exterior packaging material 10: (1) sol dispersion stabilization, (2) improvement of adhesion to the barrier layer 13 by utilizing phosphoric acid's aluminum chelating ability, (3) imparting corrosion resistance by capturing aluminum ions (passivation formation), and (4) improvement of the cohesive force of the corrosion prevention treatment layers (oxide layers) 14a, 14b by easily causing dehydration condensation of phosphoric acid even at low temperatures.

[0049] The corrosion prevention layers 14a and 14b formed from the rare earth oxide sol are aggregates of inorganic particles, and therefore may lose their cohesive strength even after the drying and curing process. Therefore, it is preferable that the corrosion prevention layers 14a and 14b in this case are compounded with an anionic polymer or a cationic polymer to compensate for the cohesive strength.

[0050] The corrosion prevention treatment layers 14a, 14b are not limited to the above-mentioned layers. For example, they may be formed using a treatment agent in which phosphoric acid and a chromium compound are mixed with a resin binder (such as aminophenol), as in the case of coating-type chromate, which is a known technology. By using this treatment agent, a layer having both corrosion prevention function and adhesion can be formed. In addition, although it is necessary to consider the stability of the coating liquid, a coating agent in which a rare earth oxide sol and a polycationic polymer or a polyanionic polymer are mixed in advance into a one-component solution can be used to form a layer having both corrosion prevention function and adhesion.

[0051] The mass per unit area of ​​the corrosion prevention layers 14a and 14b is 0.005 to 0.200 g / m2 regardless of whether the layer has a multi-layer structure or a single-layer structure. 2 is preferable, and 0.010 to 0.100 g / m 2 It is more preferable that the mass per unit area is 0.005 g / m 2 If the mass per unit area is 0.200 g / m or more, it is easy to impart a corrosion prevention function to the barrier layer 13. 2 Even if the thickness exceeds 100 mm, the corrosion prevention function does not change much. On the other hand, when a rare earth oxide sol is used, if the coating is thick, the heat curing during drying may be insufficient, which may result in a decrease in cohesive force. The thickness of the corrosion prevention layers 14a and 14b can be calculated from their specific gravity.

[0052] From the viewpoint of easily maintaining the adhesion between the sealant layer 16 and the barrier layer 13, the corrosion prevention treatment layers 14a, 14b may be in an embodiment containing, for example, cerium oxide, 1 to 100 parts by mass of phosphoric acid or a phosphate relative to 100 parts by mass of the cerium oxide, and a cationic polymer, or may be formed by subjecting the barrier layer 13 to a chemical conversion treatment, or may be formed by subjecting the barrier layer 13 to a chemical conversion treatment and contain a cationic polymer.

[0053] <Second adhesive layer> The second adhesive layer 12b is a layer that bonds the barrier layer 13 and the sealant layer 16. For the second adhesive layer 12b, a general adhesive for bonding the barrier layer 13 and the sealant layer 16 can be used.

[0054] When a second corrosion prevention treatment layer 14b is provided on the barrier layer 13 and the second corrosion prevention treatment layer 14b has a layer containing at least one polymer selected from the group consisting of the above-mentioned cationic polymers and anionic polymers, the second adhesive layer 12b is preferably a layer containing a compound (hereinafter also referred to as a "reactive compound") that is reactive with the above-mentioned polymer contained in the second corrosion prevention treatment layer 14b.

[0055] For example, when the second corrosion prevention treatment layer 14b contains a cationic polymer, the second adhesive layer 12b contains a compound reactive with the cationic polymer. When the second corrosion prevention treatment layer 14b contains an anionic polymer, the second adhesive layer 12b contains a compound reactive with the anionic polymer. When the second corrosion prevention treatment layer 14b contains a cationic polymer and an anionic polymer, the second adhesive layer 12b contains a compound reactive with the cationic polymer and a compound reactive with the anionic polymer. However, the second adhesive layer 12b does not necessarily have to contain the above two types of compounds, and may contain a compound reactive with both the cationic polymer and the anionic polymer. Here, "reactive" means to form a covalent bond with the cationic polymer or the anionic polymer. The second adhesive layer 12b may further contain an acid-modified polyolefin resin.

[0056] The compound reactive with the cationic polymer may be at least one compound selected from the group consisting of a polyfunctional isocyanate compound, a glycidyl compound, a compound having a carboxy group, and a compound having an oxazoline group.

[0057] Examples of the polyfunctional isocyanate compound, glycidyl compound, compound having a carboxy group, and compound having an oxazoline group include the polyfunctional isocyanate compound, glycidyl compound, compound having a carboxy group, and compound having an oxazoline group, which are exemplified above as crosslinking agents for forming a crosslinked structure from a cationic polymer. Among these, the polyfunctional isocyanate compound is preferred in terms of high reactivity with the cationic polymer and ease of forming a crosslinked structure.

[0058] The compound reactive with anionic polymers includes at least one compound selected from the group consisting of glycidyl compounds and compounds having oxazoline groups.These glycidyl compounds and compounds having oxazoline groups include the glycidyl compounds and compounds having oxazoline groups exemplified above as crosslinking agents for forming cationic polymers into crosslinked structures.Among these, glycidyl compounds are preferred because of their high reactivity with anionic polymers.

[0059] When the second adhesive layer 12b contains an acid-modified polyolefin resin, it is preferable that the reactive compound is also reactive with the acidic group in the acid-modified polyolefin resin (i.e., forms a covalent bond with the acidic group). This further enhances the adhesion to the second corrosion prevention treatment layer 14b. In addition, the acid-modified polyolefin resin has a crosslinked structure, which further improves the solvent resistance of the exterior material 10.

[0060] The content of the reactive compound is preferably from the same amount to 10 times the equivalent amount of the acidic group in the acid-modified polyolefin resin. If the content of the reactive compound is equal to or more than the same amount, the reactive compound will react sufficiently with the acidic group in the acid-modified polyolefin resin. On the other hand, if the content of the reactive compound exceeds 10 times the equivalent amount, the crosslinking reaction with the acid-modified polyolefin resin is sufficiently saturated, so that there is a concern of the presence of unreacted substances and the deterioration of various performances. Therefore, for example, the content of the reactive compound is preferably 5 to 20 parts by mass (solid content ratio) per 100 parts by mass of the acid-modified polyolefin resin.

[0061] The acid-modified polyolefin resin is a polyolefin resin to which an acidic group has been introduced. Examples of the acidic group include a carboxyl group, a sulfonic acid group, and an acid anhydride group, and maleic anhydride groups and (meth)acrylic acid groups are particularly preferred. For example, the acid-modified polyolefin resin may be the same as the modified polyolefin resin used in the sealant layer 16.

[0062] The second adhesive layer 12b may contain various additives such as a flame retardant, a slip agent, an antiblocking agent, an antioxidant, a light stabilizer, and a tackifier.

[0063] The second adhesive layer 12b may contain, for example, an acid-modified polyolefin and at least one curing agent selected from the group consisting of a polyfunctional isocyanate compound, a glycidyl compound, a compound having a carboxy group, a compound having an oxazoline group, and a carbodiimide compound, from the viewpoint of suppressing a decrease in laminate strength when corrosive gases such as hydrogen sulfide or an electrolyte are involved and from the viewpoint of further suppressing a decrease in insulating properties. Examples of the carbodiimide compound include N,N'-di-o-toluylcarbodiimide, N,N'-diphenylcarbodiimide, N,N'-di-2,6-dimethylphenylcarbodiimide, N,N'-bis(2,6-diisopropylphenyl)carbodiimide, N,N'-dioctyldecylcarbodiimide, N-triyl-N'-cyclohexylcarbodiimide, N,N'-di-2,2-di-t-butylphenylcarbodiimide, N-triyl-N'-phenylcarbodiimide, N,N'-di-p-nitrophenylcarbodiimide, N,N'-di-p-aminophenylcarbodiimide, N,N'-di-p-hydroxyphenylcarbodiimide, N,N'-di-cyclohexylcarbodiimide, and N,N'-di-p-toluylcarbodiimide.

[0064] In addition, as the adhesive for forming the second adhesive layer 12b, for example, a polyurethane adhesive obtained by blending polyester polyol made of hydrogenated dimer fatty acid and diol with polyisocyanate can be used. Examples of adhesives include polyurethane resins obtained by reacting a bifunctional or higher isocyanate compound with a base material such as polyester polyol, polyether polyol, acrylic polyol, or carbonate polyol, and epoxy resins obtained by reacting an amine compound with a base material having an epoxy group, which are preferable from the viewpoint of heat resistance.

[0065] The thickness of the second adhesive layer 12b is not particularly limited, but from the viewpoint of obtaining the desired adhesive strength, processability, and the like, it is preferably 1 to 10 μm, and more preferably 2 to 7 μm.

[0066] <Sealant layer 16> The sealant layer 16 is a layer that imparts heat-sealing sealability to the exterior material 10, and is a layer that is disposed on the inside and heat-sealed (thermally fused) when assembling the all-solid-state battery.

[0067] The moisture content of the sealant layer 16 is 2700 ppm by mass or less. In this case, compared to when the moisture content of the sealant layer 16 exceeds 2700 ppm by mass, the generation of bubbles in the sealant layer during heat sealing can be more effectively suppressed.

[0068] The moisture content of the sealant layer 16 is preferably 2000 ppm by mass or less, and more preferably 1500 ppm by mass or less. The moisture content of the sealant layer 16 may be 0 ppm by mass.

[0069] It is sufficient that the overall moisture content of the sealant layer 16 is 2700 ppm by mass or less. Therefore, when the sealant layer 16 is composed of a multilayer film, each layer may have a moisture content of 2700 ppm by mass or less, but even if some layers have a moisture content of 2700 ppm by mass or less and the remaining layers have a moisture content greater than 2700 ppm by mass, it is sufficient that the overall moisture content is 2700 ppm by mass or less.

[0070] As the sealant layer 16, for example, a film containing a thermoplastic resin such as a polyolefin resin, a polyester resin, a polycarbonate resin, a polyphenylene ether resin, a polyacetal resin, a polystyrene resin, a polyvinyl chloride resin, or a polyvinyl acetate resin can be used. By blending the various resins listed above to form a polymer alloy, it is possible to control the sealing suitability and heat resistance. Among them, it is preferable to use a film containing a polyolefin resin (hereinafter also referred to as a "polyolefin film") or a film containing a polyester resin (hereinafter also referred to as a "polyester film"). In this case, the sealing property to the exterior material 10 is improved. In addition, since the polyolefin film and the polyester film have heat resistance, the exterior material 10 can further improve the heat resistance of the all-solid-state battery. It is preferable that the above-mentioned thermoplastic resin does not contain a hydrophilic group component or contains a small proportion of the hydrophilic group component. In this case, since the thermoplastic resin is less likely to adsorb moisture, it is easy to make the moisture content of the sealant layer 16 2700 mass ppm or less.

[0071] Examples of polyolefin resins include polyolefin resins such as low-density, medium-density, or high-density polyethylene; ethylene-α-olefin copolymer; polypropylene; block or random copolymers containing propylene as a copolymerization component; and propylene-α-olefin copolymer. The polyolefin resin may be an acid-modified polyolefin resin obtained by modifying a polyolefin resin with acid or glycidyl. When a polyolefin film is directly laminated to the barrier layer 13 without the corrosion prevention treatment layer 14b and the second adhesive layer 12b, it is preferable that the polyolefin film contains an acid-modified polyolefin resin layer containing an acid-modified polyolefin resin, and this acid-modified polyolefin resin layer is directly laminated to the barrier layer 13. In this case, moisture is less likely to be taken in by the sealant layer 16 than when the acid-modified polyolefin resin layer of the polyolefin film is directly laminated to the barrier layer 13, and the acid-modified polyolefin resin layer of the polyolefin film and the barrier layer 13 are bonded together with a polyurethane adhesive used as a high-temperature resistant adhesive. Therefore, even if the exterior material 10 is repeatedly exposed to high temperatures, it is difficult for moisture to be released each time from the sealant layer 16. Therefore, when an all-solid-state battery contains a sulfide-based solid electrolyte as a solid electrolyte in an exterior bag, it is possible to suppress the generation of hydrogen sulfide due to a reaction between the released moisture and sulfide.

[0072] Examples of polyester resins include polyethylene terephthalate (PET) resin, polybutylene terephthalate (PBT) resin, polyethylene naphthalate (PEN) resin, polybutylene naphthalate (PBN) resin, and copolymers thereof. These polyester resins may be used alone or in combination of two or more. In addition, copolymers of any acid and glycol may be used.

[0073] In addition, the sealant layer 16 may further contain additives such as antioxidants, slip agents, flame retardants, antiblocking agents, light stabilizers, dehydrating agents, tackifiers, crystal nucleating agents, and plasticizers in order to impart sealing properties, heat resistance, and other functionalities.

[0074] The melting point of the sealant layer 16 is not particularly limited, but is preferably 150° C. or higher, more preferably 155° C. or higher, and even more preferably 160° C. or higher. When the melting point of the sealant layer 16 is 150° C. or higher, even if the exterior material 10 is used in a high-temperature environment, the seal strength of the exterior material 10 can be prevented from decreasing. Therefore, when an all-solid-state battery contains a sulfide-based solid electrolyte as a solid electrolyte in an exterior bag, even if gas such as hydrogen sulfide is generated by a reaction between moisture and the sulfide-based solid electrolyte in the exterior bag of the all-solid-state battery, leakage of such gas can be further prevented.

[0075] The melting point of the sealant layer 16 is preferably 250°C or less, more preferably 240°C or less, and even more preferably 230°C or less. In this case, the melting point of the sealant layer 16 being 250°C or less can reduce the heat sealing temperature. Therefore, the generation of bubbles in the sealant layer 16 during heat sealing can be further suppressed. Therefore, the deterioration of the seal strength and barrier property of the exterior material 10 is further suppressed. Therefore, the exterior material 10 can more sufficiently maintain the sealing property of the exterior bag of the all-solid-state battery. In addition, the exterior material 10 can also suppress the intrusion of moisture through the exterior material 10.

[0076] The sealant layer 16 may be either a single layer film or a multilayer film, and may be selected according to the required function. When the sealant layer 16 is a multilayer film, the layers may be laminated by coextrusion or dry lamination. However, when the sealant layer 16 is a multilayer film, it is preferable to use the same type of resin from the viewpoint of interlayer adhesion. For example, a layer containing a modified polyolefin resin may be disposed in contact with the barrier layer 13, and one layer of a non-modified polyolefin resin may be extruded or multiple layers of polyolefin resin may be coextruded and laminated on the layer.

[0077] The thickness of the sealant layer 16 is not particularly limited, but is preferably 10 to 100 μm, and more preferably 20 to 60 μm. When the thickness of the sealant layer 16 is 10 μm or more, sufficient sealing strength can be obtained. When the thickness of the sealant layer 16 is 100 μm or less, the amount of water vapor penetrating from the peripheral portion of the packaging material 10 can be reduced.

[0078] <Hydrogen sulfide decomposition and adsorption material> When the exterior material 10 is used in an all-solid-state battery having a sulfide-based solid electrolyte, at least one of the layers constituting the exterior material 10 of the present embodiment may contain a hydrogen sulfide decomposition / adsorption material that decomposes or adsorbs hydrogen sulfide. In this case, even if hydrogen sulfide is generated by reaction between water and a sulfide-based solid electrolyte in an all-solid-state battery, the hydrogen sulfide is prevented from permeating the exterior material 10. The hydrogen sulfide decomposition / adsorption material is contained in, for example, the first adhesive layer 12a, the second adhesive layer 12b, the sealant layer 16, or at least one of these. In particular, the hydrogen sulfide decomposition / adsorption material is preferably contained in the sealant layer 16. In this case, the hydrogen sulfide is effectively prevented from permeating the exterior material 10.

[0079] Examples of hydrogen sulfide decomposition and adsorption materials include zinc oxide, amorphous metal silicates (mainly those in which the metal is copper or zinc), hydrates of zirconium and tantanide elements, tetravalent metal phosphates (particularly those in which the metal is copper), mixtures of zeolite and zinc ions, mixtures of zeolite, zinc oxide, and copper (II) oxide, potassium permanganate, sodium permanganate, silver sulfate, silver acetate, aluminum oxide, iron hydroxide, isocyanate compounds, aluminum silicate, potassium aluminum sulfate, zeolite, activated carbon, amine compounds, and ionomers. In addition, the hydrogen sulfide decomposition and adsorption material is preferably one that contains zinc oxide (ZnO) and / or zinc ions, from the viewpoints of ease of detoxifying hydrogen sulfide, cost, and ease of handling. The hydrogen sulfide decomposition and adsorption material can be used alone or in combination of two or more types.

[0080] The hydrogen sulfide decomposition and adsorption material may be a deodorizer that has a deodorizing effect on hydrogen sulfide, such as "Daimshoo PE-M 3000-Z" (polyethylene masterbatch product) manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd., "Kesmon" manufactured by Toagosei Co., Ltd., "Shoe Cleanse" manufactured by Rasa Kogyo Co., Ltd., and "Dashlight ZU" and "Dashlight CZU" manufactured by Sinanen Zeomic Co., Ltd.

[0081] Metal soap such as zinc stearate may be added to the layer containing the hydrogen sulfide decomposition adsorption material in order to improve the dispersibility of the hydrogen sulfide decomposition adsorption material. By using the hydrogen sulfide decomposition adsorption material in combination with a metal soap, the dispersibility of the hydrogen sulfide decomposition adsorption material in the layer can be increased, making it difficult for the effect of detoxifying hydrogen sulfide to be biased, and making it easier to suppress a decrease in the function (e.g., adhesion strength, seal strength, etc.) of the layer containing the hydrogen sulfide decomposition adsorption material.

[0082] The hydrogen sulfide decomposition / adsorption material may be used in the form of a master batch. When the hydrogen sulfide decomposition and adsorption material is to be blended into the sealant layer 16, a high concentration blend may be prepared in advance as a master batch, and then the master batch may be blended into the resin of the sealant layer 16 to obtain an appropriate concentration. When the hydrogen sulfide decomposition and adsorption material is blended in the first adhesive layer 12a or the second adhesive layer 12b, it may be blended directly into the coating when the first adhesive layer 12a or the second adhesive layer 12b is coated, or when the first adhesive layer 12a or the second adhesive layer 12b is formed by extrusion or the like, it may be blended in a master batch prepared in the same manner as the sealant layer 16. When preparing a master batch, the resin may be a thermoplastic resin such as a polyolefin resin, a polyamide resin, a polyester resin, a polycarbonate resin, a polyphenylene ether resin, a polyacetal resin, a polystyrene resin, a polyvinyl chloride resin, or a polyvinyl acetate resin.

[0083] The content of the hydrogen sulfide decomposition adsorption material in the layer containing the hydrogen sulfide decomposition adsorption material may be 0.01% by mass to 30% by mass, 0.05% by mass to 20% by mass, or 0.1% by mass to 15% by mass, based on the total amount of the layer. When the content of the hydrogen sulfide decomposition adsorption material is equal to or more than the lower limit, the effect of detoxifying hydrogen sulfide is easily obtained, and when the content is equal to or less than the upper limit, deterioration of the function (e.g., adhesion strength, seal strength, etc.) of the layer containing the hydrogen sulfide decomposition adsorption material can be suppressed.

[0084] Although the preferred embodiment of the exterior material for an all-solid-state battery of the present embodiment has been described in detail above, the present disclosure is not limited to such a specific embodiment.

[0085] For example, FIG. 1 shows a case where anti-corrosion treatment layers 14a, 14b are provided on both sides of the barrier layer 13, but only one of the anti-corrosion treatment layers 14a, 14b may be provided, or no anti-corrosion treatment layer may be provided.

[0086] 1 shows a case where the barrier layer 13 and the sealant layer 16 are laminated using the second adhesive layer 12b, but the barrier layer 13 and the sealant layer 16 may be laminated using an adhesive resin layer 15 as in the all-solid-state battery packaging material 20 shown in Fig. 2. In addition, in the all-solid-state battery packaging material 20 shown in Fig. 2, the second adhesive layer 12b may be provided between the barrier layer 13 and the adhesive resin layer 15.

[0087] <Adhesive resin layer 15> The adhesive resin layer 15 is generally composed of an adhesive resin composition as a main component and additive components as necessary. The adhesive resin composition is not particularly limited, but preferably contains a modified polyolefin resin.

[0088] The modified polyolefin resin is preferably a polyolefin resin graft-modified with an unsaturated carboxylic acid derivative derived from an unsaturated carboxylic acid, an acid anhydride, or an ester thereof.

[0089] Examples of polyolefin resins include low density polyethylene, medium density polyethylene, high density polyethylene, ethylene-α-olefin copolymer, homopolypropylene, block polypropylene, random polypropylene, and propylene-α-olefin copolymer.

[0090] The modified polyolefin resin is preferably a polyolefin resin modified with maleic anhydride. For example, "Admer" manufactured by Mitsui Chemicals, Inc. and "Modic" manufactured by Mitsubishi Chemical Corporation are suitable for the modified polyolefin resin. Since such modified polyolefin resins have excellent reactivity with various metals and polymers having various functional groups, the adhesive resin layer 15 can be given adhesion by utilizing the reactivity. In addition, the adhesive resin layer 15 may contain various additives such as various compatible and incompatible elastomers, flame retardants, slip agents, antiblocking agents, antioxidants, light stabilizers, and tackifiers, as necessary.

[0091] The thickness of the adhesive resin layer 15 is not particularly limited, but from the viewpoints of stress relaxation and moisture permeability, it is preferably the same as or less than that of the sealant layer 16 .

[0092] In addition, in the all-solid-state battery exterior material 20, the total thickness of the adhesive resin layer 15 and the sealant layer 16 is preferably in the range of 5 to 100 μm, and more preferably in the range of 20 to 80 μm, from the viewpoint of achieving both a thin film and improved heat seal strength in a high-temperature environment.

[0093] In the exterior packaging material 20, the hydrogen sulfide decomposition / adsorbing material may be contained in the adhesive resin layer 15. In the exterior packaging material 20, the hydrogen sulfide decomposition / adsorbing material may be contained in at least one layer selected from the group consisting of the first adhesive layer 12a, the adhesive resin layer 15, and the sealant layer 16.

[0094] The exterior material of the present disclosure may further include a protective layer 17 arranged on the surface of the base material layer 11 opposite to the barrier layer 13, as in the exterior material 30 for an all-solid-state battery shown in Fig. 3. In Fig. 3, the adhesive resin layer 15 may be a second adhesive layer 12b.

[0095] <Protective layer 17> The protective layer 17 is a layer that protects the base layer 11. The same material as that of the first adhesive layer 12a can be used as a material constituting the protective layer 17. The protective layer 17 can be formed on the base layer 11 by coating or the like.

[0096] In the exterior packaging material 30, the hydrogen sulfide decomposition / adsorption material may be contained in the protective layer 17. In the exterior packaging material 30, the hydrogen sulfide decomposition / adsorption material may be contained in at least one layer selected from the group consisting of the protective layer 17, the first adhesive layer 12a, the adhesive resin layer 15, and the sealant layer 16.

[0097] [Exterior material manufacturing method] Next, there will be described an example of a method for manufacturing the exterior packaging material 10 shown in Fig. 1. Note that the method for manufacturing the exterior packaging material 10 is not limited to the following method.

[0098] The manufacturing method of the exterior material 10 of this embodiment is roughly composed of a step of providing corrosion prevention treatment layers 14a, 14b on the barrier layer 13, a step of bonding the base material layer 11 and the barrier layer 13 together using a first adhesive layer 12a, a step of further laminating a sealant layer 16 via a second adhesive layer 12b to produce a laminate, and a step of, if necessary, subjecting the obtained laminate to an aging treatment.

[0099] (Laminating process of corrosion prevention treatment layer onto barrier layer) This step is a step of forming the corrosion prevention treatment layers 14a, 14b on the barrier layer 13. As described above, examples of the method include subjecting the barrier layer 13 to a degreasing treatment, a hydrothermal conversion treatment, an anodizing treatment, or a chemical conversion treatment, or applying a coating agent having corrosion prevention properties.

[0100] Furthermore, when the corrosion prevention treatment layers 14a, 14b are multiple layers, for example, a coating liquid (coating agent) constituting the lower corrosion prevention treatment layer (barrier layer 13 side) may be applied to the barrier layer 13 and baked to form a first layer, and then a coating liquid (coating agent) constituting the upper corrosion prevention treatment layer may be applied to the first layer and baked to form a second layer.

[0101] The degreasing treatment may be performed by spraying or immersion. The hydrothermal conversion treatment and anodizing treatment may be performed by immersion. The chemical conversion treatment may be performed by an appropriate method such as immersion, spraying, or coating, depending on the type of chemical conversion treatment.

[0102] Regarding the coating method of the coating agent having corrosion prevention properties, various methods such as gravure coating, reverse coating, roll coating, bar coating, etc. can be used.

[0103] As described above, the various treatments may be performed on either one or both sides of the metal foil, but in the case of one-sided treatment, the treated side is preferably the side on which the sealant layer 16 is laminated. If required, the surface of the base layer 11 may also be subjected to the above treatments.

[0104] The amount of coating agent applied to form the first layer and the second layer is 0.005 to 0.200 g / m 2 is preferable, and 0.010 to 0.100 g / m 2 is more preferred.

[0105] Furthermore, when dry curing is required, it can be performed at a base material temperature in the range of 60 to 300° C. depending on the drying conditions of the corrosion prevention treatment layers 14a and 14b used.

[0106] (Laminating process of substrate layer and barrier layer) This step is a step of bonding the barrier layer 13 provided with the corrosion prevention treatment layers 14a, 14b to the base material layer 11 via the first adhesive layer 12a. The bonding method may be dry lamination, non-solvent lamination, wet lamination, or the like, and the two are bonded together using the material constituting the first adhesive layer 12a described above. The first adhesive layer 12a has a dry coating amount of 1 to 10 g / m. 2 More preferably, the range is 2 to 7 g / m 2 It is set within the range.

[0107] (Lamination process of second adhesive layer and sealant layer) This step is a step of bonding the sealant layer 16 via the second adhesive layer 12b to the second corrosion prevention treatment layer 14b side of the barrier layer 13. Examples of the bonding method include a wet process and dry lamination.

[0108] In the case of the wet process, the solution or dispersion of the adhesive constituting the second adhesive layer 12b is applied onto the second corrosion prevention treatment layer 14b, the solvent is evaporated at a predetermined temperature to form a dry film, and a baking process is further performed as necessary. After that, the sealant layer 16 is laminated to manufacture the exterior material 10. Examples of the application method include the various application methods exemplified above. The preferred dry application amount of the second adhesive layer 12b is the same as that of the first adhesive layer 12a.

[0109] In this case, the sealant layer 16 can be produced, for example, by a melt extrusion molding machine using a resin composition for forming a sealant layer that contains the above-mentioned components of the sealant layer 16. In the melt extrusion molding machine, the processing speed can be set to 80 m / min or more from the viewpoint of productivity.

[0110] (Aging process) This step is a step of aging (curing) the laminate. By aging the laminate, it is possible to promote adhesion between the barrier layer 13, the second corrosion prevention treatment layer 14b, the second adhesive layer 12b, and the sealant layer 16. The aging treatment can be carried out at a temperature in the range of room temperature to 100°C. The aging time is, for example, 1 to 10 days.

[0111] In this manner, the exterior packaging material 10 of the present embodiment as shown in FIG. 1 can be manufactured.

[0112] Next, a description will be given of an example of a method for manufacturing the exterior material 20 shown in Fig. 2. Note that the method for manufacturing the exterior material 20 is not limited to the following method.

[0113] The manufacturing method of the exterior material 20 of this embodiment is generally configured to include a step of providing the corrosion prevention treatment layers 14a, 14b on the barrier layer 13, a step of bonding the base material layer 11 and the barrier layer 13 together using the first adhesive layer 12a, a step of further laminating the adhesive resin layer 15 and the sealant layer 16 to prepare a laminate, and a step of heat treating the obtained laminate, if necessary. Note that the steps up to the step of bonding the base material layer 11 and the barrier layer 13 can be performed in the same manner as the manufacturing method of the exterior material 10 described above.

[0114] (Laminating process of adhesive resin layer and sealant layer) This step is a step of forming an adhesive resin layer 15 and a sealant layer 16 on the second corrosion prevention treatment layer 14b formed in the previous step. The method includes a method of sand laminating the adhesive resin layer 15 together with the sealant layer 16 using an extrusion laminator. Furthermore, lamination is also possible by a tandem lamination method in which the adhesive resin layer 15 and the sealant layer 16 are extruded, or a co-extrusion method. In forming the adhesive resin layer 15 and the sealant layer 16, for example, each component is blended so as to satisfy the above-mentioned configuration of the adhesive resin layer 15 and the sealant layer 16. The above-mentioned resin composition for forming the sealant layer is used to form the sealant layer 16.

[0115] This process produces a laminate in which the layers are stacked in the following order: base layer 11 / first adhesive layer 12a / first corrosion prevention treatment layer 14a / barrier layer 13 / second corrosion prevention treatment layer 14b / adhesive resin layer 15 / sealant layer 16, as shown in FIG. 2.

[0116] The adhesive resin layer 15 may be laminated by directly extruding the materials dry-blended to have the above-mentioned material composition using an extrusion laminator. Alternatively, the adhesive resin layer 15 may be laminated by extruding the granulated material, which has been melt-blended in advance using a melt kneading device such as a single-screw extruder, a twin-screw extruder, or a Brabender mixer, using an extrusion laminator.

[0117] The sealant layer 16 may be laminated by directly extruding the materials dry-blended to have the above-mentioned material composition as the constituents of the resin composition for forming the sealant layer using an extrusion laminator. Alternatively, the adhesive resin layer 15 and the sealant layer 16 may be laminated by a tandem lamination method in which the adhesive resin layer 15 and the sealant layer 16 are extruded using an extrusion laminator using a granulated product obtained by melt blending in advance using a melt kneading device such as a single screw extruder, a twin screw extruder, or a Brabender mixer, or by a co-extrusion method. Alternatively, a sealant monolayer may be formed in advance as a cast film using the resin composition for forming the sealant layer, and this film may be laminated together with an adhesive resin by a method of sand lamination. The forming speed (processing speed) of the adhesive resin layer 15 and the sealant layer 16 may be, for example, 80 m / min or more from the viewpoint of productivity.

[0118] (Heat treatment process) This step is a step of heat-treating the laminate. Heat-treating the laminate can improve adhesion between the barrier layer 13, the second corrosion prevention treatment layer 14b, the adhesive resin layer 15, and the sealant layer 16. As a method of heat treatment, it is preferable to treat at a temperature at least equal to or higher than the melting point of the adhesive resin layer 15.

[0119] In this manner, the exterior packaging material 20 of this embodiment as shown in FIG. 2 can be manufactured.

[0120] [All-solid battery] FIG. 4 is a perspective view showing one embodiment of an all-solid-state battery produced using the above-mentioned exterior material 10. As shown in FIG. 4, the all-solid-state battery 50 includes a battery body 52 having a sulfide-based electrolyte as a solid electrolyte, two metal terminals (current extraction terminals) 53 for extracting current from the battery body 52 to the outside, and an exterior bag 54 that hermetically encloses the battery body 52. ​​The exterior bag 54 is obtained by heat-sealing the exterior material 10 according to the present embodiment described above, and is used as a container for accommodating the battery body 52. ​​In the exterior material 10, the base material layer 11 is the outermost layer, and the sealant layer 16 is the innermost layer. That is, the exterior material 10 is configured to enclose the battery body 52 inside by folding one laminate film in two and heat-sealing the periphery, or by overlapping two laminate films and heat-sealing the periphery, so that the base material layer 11 is on the outer side of the all-solid-state battery 50 and the sealant layer 16 is on the inner side of the all-solid-state battery 50. The metal terminal 53 is sandwiched by an exterior bag 54 with the sealant layer 16 on the inside. The metal terminal 53 may be sandwiched by the exterior bag 54 via a tab sealant.

[0121] The battery body 52 has at least one power generating element consisting of a positive electrode, a solid electrolyte, and a negative electrode. The metal terminal 53 is a part of the current collector taken out from the exterior material 10, and is made of a metal foil such as copper foil or aluminum foil.

[0122] According to the all-solid-state battery 50, the exterior bag 54 is obtained by heat-sealing the exterior material 10. Here, the exterior material 10 can suppress the generation of air bubbles in the sealant layer 16 during heat sealing. Therefore, according to the all-solid-state battery 50, the sealant layer 16 of the exterior material 10 is prevented from having rough and dense parts, which causes the seal strength to decrease in the rough parts. Therefore, even if the battery body 52 expands due to use of the all-solid-state battery 50 in a high-temperature environment and a force acts on the exterior bag 54 to open it, the all-solid-state battery 50 can maintain the sealed state of the exterior bag 54 by the exterior material 10. As a result, even if hydrogen sulfide is generated in the exterior bag 54, the hydrogen sulfide is prevented from leaking from the exterior bag 54. In addition, the sealant layer 16 is prevented from generating air bubbles that easily become a passage for moisture, so that the intrusion of moisture from the outside of the exterior material 10 is suppressed. As a result, it is possible to suppress the generation of hydrogen sulfide due to a reaction between moisture and a sulfide-based electrolyte.

[0123] In the all-solid-state battery 50, the exterior bag 54 may be obtained by heat-sealing the exterior material 20 or the exterior material 30 instead of the exterior material 10. In addition, the solid electrolyte is not limited to a sulfide-based solid electrolyte, and may be an oxide-based solid electrolyte or the like. EXAMPLES

[0124] The present disclosure will be described more specifically below based on examples, but the present disclosure is not limited to the following examples.

[0125] <Materials used> The materials used in the examples and comparative examples are shown below.

[0126] (base material layer) As the substrate layer, the following films were used. Semi-aromatic polyamide (nylon 9T) film (manufactured by Unitika Ltd., melting point: 305°C)

[0127] (First adhesive layer) For the first adhesive layer, a polyurethane adhesive (manufactured by Toyo Ink Co., Ltd.) was used, which is a mixture of a polyester polyol-based base agent and a tolylene diisocyanate adduct-based curing agent.

[0128] (First corrosion prevention treatment layer and second corrosion prevention treatment layer) The first corrosion prevention treatment layer (on the substrate layer side) and the second corrosion prevention treatment layer (on the sealant layer side) were formed using the following (CL-1) and (CL-2). (CL-1): Sodium polyphosphate-stabilized cerium oxide sol adjusted to a solid content of 10% by mass using distilled water as a solvent. In the sodium polyphosphate-stabilized cerium oxide sol, 10 parts by mass of sodium phosphate was mixed with 100 parts by mass of cerium oxide. (CL-2): A composition prepared by using distilled water as a solvent and adjusting the solid content concentration to 5% by mass. In the composition, the ratio of "polyallylamine (manufactured by Nitto Boseki Co., Ltd.)" to "polyglycerol polyglycidyl ether (manufactured by Nagase ChemteX Corporation)" was 90:10 (mass ratio).

[0129] (Barrier layer) As the barrier layer, a soft aluminum foil that had been annealed and degreased (manufactured by Toyo Aluminum Co., Ltd., product name: 8079 material, thickness: 40 μm) was used.

[0130] (Second adhesive layer) As the first adhesive layer, the same polyurethane adhesive (manufactured by Toyo Ink Mfg. Co., Ltd., product name: TM-K55) as the first adhesive layer was used.

[0131] (Sealant layer) The following films were used as the sealant layers. Polyolefin film 1 (PO film 1, polypropylene-polyethylene random copolymer, manufactured by Futamura Chemical Co., Ltd., product name: FHK2, thickness: 40 μm, melting point: 135° C., moisture content: 516 ppm by mass) Polyolefin film 2 (PO film 2, acid-modified polypropylene (thickness: 12.5 μm, melting point: 160°C) and polypropylene (thickness: 12.5 μm, melting point: 160°C) laminate (melting point: 160°C, thickness: 25 μm, moisture content: 546 mass ppm) Polyester film 1 (polyethylene terephthalate, manufactured by Unitika Ltd., product name: Emblet, thickness: 25 μm, melting point: 257°C, moisture content: 2682 ppm by mass) Polyester film 2 (polyethylene naphthalate, manufactured by Toyobo Co., Ltd., product name: Teonex, thickness: 25 μm, melting point: 265° C., moisture content: 2637 ppm by mass) Polyester film 3 (a copolymer of multiple types of polyethylene terephthalate, manufactured by Unitika Ltd., thickness: 25 μm, melting point: 210°C, moisture content: 1648 ppm by mass) Polyamide film (PA film, nylon 6, manufactured by Toyobo Co., Ltd., product name: Harden N1102, thickness: 25 μm, melting point: 225°C, moisture content: 23729 ppm by mass) The moisture content was measured as follows. That is, the film cut into 10 cm squares was left in an environment of 23°C / 50%RH for two days, and then heated using a thermal moisture vaporizer (manufactured by HIRANUMA Co., Ltd., product name: EV-2000) set at 300°C, and the amount of moisture generated was measured using a trace moisture measuring device (Karl Fischer: "AQ-2100" manufactured by HIRANUMA Co., Ltd.). At this time, dry N2 gas was used as the carrier gas. Then, the moisture content was calculated based on the following formula using the moisture amount measured as described above. Moisture content (mass ppm) = measured moisture content (g) / film mass (g)

[0132] (Examples 1 to 4) First, a first corrosion prevention treatment layer and a second corrosion prevention treatment layer were provided on the barrier layer by the following procedure: First, (CL-1) was applied to both sides of the barrier layer in a dry coating amount of 70 mg / m 2The layer was then coated by microgravure coating so that the thickness of the layer was 200 mm, and the layer was baked at 200° C. in a drying unit. Next, (CL-2) was applied to the layer obtained in a dry coating amount of 20 mg / m 2 The coating was performed by microgravure coating so that the thickness of the coating was 100 μm. In this way, composite layers made of (CL-1) and (CL-2) were formed on both sides of the barrier layer as the first and second corrosion prevention treatment layers, respectively, to obtain a first laminate. These composite layers exhibit corrosion prevention performance by combining the two types of materials, (CL-1) and (CL-2).

[0133] Next, the first anti-corrosion treatment layer side of the barrier layer (first laminate) provided with the first anti-corrosion treatment layer and the second anti-corrosion treatment layer was attached to the base layer by a dry lamination technique using a polyurethane adhesive (first adhesive layer), to obtain a laminate (second laminate) of the first laminate and the base layer. Specifically, the polyurethane adhesive was applied to the surface of the barrier layer facing the first anti-corrosion treatment layer so that the thickness after curing was 5 μm, and then dried at 80° C. for 1 minute, laminated with the base layer, and aged at 60° C. for 120 hours to obtain the second laminate.

[0134] Next, the laminate (second laminate) including the barrier layer and the base layer was set on the unwinding section of an extrusion laminator, and a polyurethane adhesive (second adhesive layer) was used to attach the second corrosion prevention treatment layer to a sealant layer of the type shown in Table 1 by dry lamination to obtain a structure. Specifically, the polyurethane adhesive was applied to the surface of the barrier layer facing the second corrosion prevention treatment layer so that the thickness after curing would be 5 μm, and the adhesive was dried at 80° C. for 1 minute, and then laminated with the sealant layer of the type shown in Table 1, and aged at 60° C. for 120 hours to obtain a structure.

[0135] In this way, an exterior material (a laminate of substrate layer / first adhesive layer / first corrosion prevention treatment layer / barrier layer / second corrosion prevention treatment layer / second adhesive layer / sealant layer) was obtained.

[0136] Example 5 An exterior material (a laminate of substrate layer / first adhesive layer / first corrosion prevention treatment layer / barrier layer / second corrosion prevention treatment layer / sealant layer) was produced in the same manner as in Example 1, except that the laminate of the barrier layer and substrate layer was set on the unwinding section of an extrusion laminator, and a sealant layer of the type shown in Table 1 was attached onto the second corrosion prevention treatment layer by thermal lamination to obtain a structure. At this time, the thermal lamination of the second laminate including the barrier layer and substrate layer with the sealant layer was performed by heating at a temperature of 190°C under a pressure of 0.5 MPa.

[0137] Comparative Example 1 An exterior material (a laminate of substrate layer / first adhesive layer / first corrosion prevention treatment layer / barrier layer / second corrosion prevention treatment layer / second adhesive layer / sealant layer) was prepared in the same manner as in Example 1, except that the type of sealant layer shown in Table 1 was used as the sealant layer.

[0138] <Exterior material evaluation> The exterior material was cut into a size of 120 mm x 60 mm, folded in half so that the sealant layer was on the inside, and both ends of the exterior material in the longitudinal direction were overlapped, and these ends were heat-sealed for 3 seconds at a temperature of the melting point of the sealant layer + 20 ° C. while being pressurized with a pressure of 0.5 MPa, forming a heat-sealed part with a width of 10 mm (shaded part in Figure 5), and a structure was produced. Thereafter, the structure was stored at room temperature for 12 hours. Thereafter, a central part in the longitudinal direction of the heat-sealed part was cut out from the structure with a width of 15 mm x 30 mm (see Figure 5) to produce an evaluation sample. Then, this evaluation sample was separated into two separated pieces at the heat-sealed part. Then, the sealant layer of the separated separated pieces was visually observed, and the state of bubble generation in the sealant layer was evaluated based on the following criteria. The results are shown in Table 1. In addition, when the sealant layer is a multilayer film, the "melting point of the sealant layer" was the melting point of the layer with the lowest melting point among the layers constituting the multilayer film. (Evaluation Criteria) ◎: No bubbles are observed ○: Localized air bubbles are observed ×: Air bubbles are observed all over the surface

[0139] [Table 1]

[0140] The results shown in Table 1 show that the packaging materials of Examples 1 to 6, which have a moisture content of 2700 ppm by mass or less, suppress the generation of air bubbles compared to the packaging material of Comparative Example 1, which has a moisture content of more than 2700 ppm by mass.

[0141] Therefore, it was confirmed that the exterior packaging material for an all-solid-state battery according to the present disclosure can suppress the generation of air bubbles during heat sealing. [Explanation of symbols]

[0142] Reference Signs List 10, 20, 30...exterior material for all-solid-state battery, 11...substrate layer, 12a...first adhesive layer, 12b...second adhesive layer, 13...barrier layer, 14a...first corrosion prevention treatment layer, 14b...second corrosion prevention treatment layer, 15...adhesive resin layer, 16...sealant layer, 17...protective layer, 50...all-solid-state battery, 52...battery body, 53...metal terminal, 54...outer bag.

Claims

1. An exterior material for an all-solid-state battery, comprising at least a substrate layer, a barrier layer, and a sealant layer in this order, the sealant layer is a polyester film containing a polyester-based resin, The sealant layer has a moisture content of 1648 ppm by mass or more and 2700 ppm by mass or less.

2. The exterior material for an all-solid-state battery according to claim 1 , wherein the sealant layer has a melting point of 250° C. or lower.

3. The exterior material for an all-solid-state battery according to claim 1 or 2, wherein the sealant layer has a melting point of 150° C. or higher.

4. A battery body including a solid electrolyte; and an outer bag for accommodating the battery body; The all-solid-state battery, wherein the outer packaging bag is obtained by heat-sealing the outer packaging material for an all-solid-state battery according to any one of claims 1 to 3.